Corpus Linguistic Research: Analyze The Use of Possessive Pronoun in P.S I Still Love You Novel By Jenny Han - Eksita Duta Nalindra (Faculty of Education and Teachers Training, 2021)
In this article, the researchers talk about the possessive pronoun found in a novel by Jenny Han entitled